Analisis Positioning dengan Menggunakan Multidimensional Scaling Nonmetrik - Devy Sintya Putri; Sri Wahyuningsih; Rito Goejantoro (Program Studi Statistika FMIPA Universitas Mulawarman, 2018)
As the era progresses, more and more smartphone brands are present in the market in which it is difficult for consumers to decide which smart phone brands are good among others. The aims of this research are to know the position of five brands of the smart phone based on the consumer perception by using multidimensional scaling analysis (MDS) and also to know the superiority for each of these smartphone brands based also on the consumer perception focused on the product attribute and consumer perception about smartphone brands which they mostly prefered. So the result indicates that the coordinate points got based on the consumer perception by using MDS analysis are as follows; Asus is (10,494,2525), Oppo is (-4,154; 3,591), Samsung is (-4,216; (- 3,979)), Sony is (4,188 ; (- 3,985)), and Xiaomi is (-6,312; 1,848). Among the five smart phone brands above, Xiaomi has an advantage on the most affordable price attribute. Samsung has an advantage on the attributes of good screen display results, better known brands, more beautiful designs, complete features, ease for use, and large memory capacity. The smart phone brands of Asus, Oppo and Sony have the advantage on the results of a good camera and good processor performance. It is the fact that the most superior smart phone brands based on the consumer’s perception data are the brand of Oppo and Samsung smart phones.